Management of Worsening Aortic Dilation and Insufficiency in a 20-Week Pregnant Woman: A Case Report - Amy Shah; Johanna Schwarzenberger; Dorina Gui; Richard Hong; Angela Chen (Hindawi Limited, 2011)
Preexisting aortic disease can worsen during pregnancy as physiologic hemodynamic changes evolve. At a large academic institution, a patient with a remote history of vasculitis presented with a second trimester pregnancy with increasing aortic dilatation and aortic insufficiency. Extensive obstetric discussions encompassed maternal cardiac risks from continuing the pregnancy and fetal risks from maternal cardiac intervention. This patient desired termination of pregnancy to avoid further complications and to expedite surgical aortic repair.